Reszinate—A Phase 1/2 Randomized Clinical Trial of Zinc and Resveratrol Utilizing Home Patient-Obtained Nasal and Saliva Viral Sampling - Kaplan, Henry G.; Wang, Kai; Reeves, Kimberly M.; Scanlan, James M.; Nunn, Christopher C.; Kieper, Douglas A.; Mark, Joshua L.; Lee, Inyoul; Liu, Rachel; Jin, Ruyun; Bolton, Michael J.; Goldman, Jason D. (Frontiers in Drug Discovery, 2022)
Background: Safe, effective, and inexpensive treatment for COVID-19 is an urgent unmet medical need. Zinc and resveratrol have been reported to have antiviral activity, and resveratrol may increase zinc activity at the site of replication by increasing intracellular zinc concentrations. Methods: A 1:1 randomized, placebo-controlled trial of zinc 150 mg plus resveratrol 4 g daily for 5 days versus placebos in outpatients with SARS-CoV-2 was carried out from 9/21/2020–1/22/2021 in Seattle, Washington. Viral shedding was followed with patient self-collected nasal and saliva samples by measuring qRT-PCR for SARS-CoV-2 N gene days 1–7, 10, and 14. Patients filled out a web-based questionnaire on days 1–14 to report symptoms, vital signs and adherence to the study intervention. The study was posted as Clinical Trials.gov NCT04542993 on 9 September 2020. Results: A total of 30 participants (14 treatment; 16 placebos) had ≥1 day of the protocol treatment and were evaluable for the primary or secondary outcome. There was no difference in viral shedding between groups, nor in the resolution of symptoms. There was a trend toward a more rapid decrease in symptoms in the treatment group, though this was not statistically significant in the GLM model. Viral shedding was similar between patient self-collected mid-turbinate nasal swabs and expectorated saliva samples with a good correlation. Conclusion: SARS-CoV-2 shedding and COVID-19 symptoms were not statistically significantly decreased by treatment. Viral shedding correlates well between patient-obtained home nasal swabs and saliva sampling.